2019
DOI: 10.1097/ta.0000000000002295
|View full text |Cite
|
Sign up to set email alerts
|

How low can you go: Achieving postoperative outpatient pain control without opioids

Abstract: BACKGROUND Postoperative outpatient narcotic overprescription plays a significant role in the opioid epidemic. Outpatient opioid prescription ranges from 150 to 350 oral morphine equivalent (OME) for a laparoscopic cholecystectomy or appendectomy, with 75 OME (10 pills of 5 mg of oxycodone) being the lowest recommendation (National Institute on Drug Abuse, 2018). We hypothesized that the addition of nonopioid medications to the outpatient pain control regimen would decrease the need for narcotics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Pain as a fifth vital sign is a bitter experience for almost all perioperative children, but good postoperative pain management is essential in accelerating recovery. Although opioids remain the mainstay of treatment for pain control, their use can have side effects such as suppression of gastrointestinal function, respiratory depression, and postoperative nausea and vomiting, significantly affecting the patient's recovery and prolonging the hospital stay [7][8][9]. Multi-modal analgesia (MMA), including acetaminophen, nonsteroidal anti-inflammatory drugs (ibuprofen), regional nerve blocks, local infiltrates of incisions, and epidural labor pain, has received much attention in recent years for substantially reducing opioid analgesics [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Pain as a fifth vital sign is a bitter experience for almost all perioperative children, but good postoperative pain management is essential in accelerating recovery. Although opioids remain the mainstay of treatment for pain control, their use can have side effects such as suppression of gastrointestinal function, respiratory depression, and postoperative nausea and vomiting, significantly affecting the patient's recovery and prolonging the hospital stay [7][8][9]. Multi-modal analgesia (MMA), including acetaminophen, nonsteroidal anti-inflammatory drugs (ibuprofen), regional nerve blocks, local infiltrates of incisions, and epidural labor pain, has received much attention in recent years for substantially reducing opioid analgesics [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested a potential concern, the evidence is of low quality and current opinion is that it should not subvert multimodal pain therapy 31 32. Sim et al 33 show in postoperative outpatients after general surgery, lower amounts of opioids were necessary when combined with courses of ibuprofen or ACET. Additionally, Hamrick et al 12 notes that when multimodal pain management is used properly, opioid use can be reduced without compromising any patient comfort.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Among a recent cohort of patients undergoing both laparoscopic cholecystectomies and appendectomies, the average number of opioid pills taken postdischarge was 1.8 oxycodone pills. 15 Recent opioid prescribing recommendations for patients undergoing a laparoscopic cholecystectomy range from 0 to 15 oxycodone or equivalent pills. 16 17 …”
Section: Methodsmentioning
confidence: 99%
“…Prescription of opioids at discharge occurs in up to 94% of cases after urgent and non-urgent laparoscopic cholecystectomies,14 and is associated with persistent opioid use among approximately 6% of patients 2. Among a recent cohort of patients undergoing both laparoscopic cholecystectomies and appendectomies, the average number of opioid pills taken postdischarge was 1.8 oxycodone pills 15. Recent opioid prescribing recommendations for patients undergoing a laparoscopic cholecystectomy range from 0 to 15 oxycodone or equivalent pills 16 17…”
Section: Methodsmentioning
confidence: 99%